PELATIHAN PENYUSUNAN PERANGKAT PEMBELAJARAN BERBASIS REALISTIC MATHEMATICS EDUCATION (RME) BAGI GURU DI KECAMATAN TEHORU DAN TELUTIH - Mananggel, Marlin Blandy; Mataheru, Wilmintjie; Salamor, Reinhard (Universitas Pattimura, 2022)
Mathematics learning is currently still focused on material goals, which means that students passively accept mathematical knowledge as